Designing an Alternative Test through Quizegg for the First Grade Students at SMK Muhammadiyah 1 Moyudan in Academic Year 2015/2016 - Rozanah Katrina Herda; Imam Ghozali (Universitas Sarjanawiyata Tamansiswa, 2019)
The objectives of the study are to describe (1) the quality of the existing test administration conducted to the first grade students of SMK Muhammadiyah 1 Moyudan in academic year 2015/2016, (2) the development of alternative test using QuizEgg for the first grade students of SMK Muhammadiyah 1 Moyudan in academic year 2015/2016, (3) the effectiveness of the developed alternative test through QuizEgg for the first grade students of SMK Muhammadiyah 1 Moyudan in academic year 2015/2016, and (4) the strengths and limitations of the developed alternative test through QuizEgg for the first grade students of SMK Muhammadiyah 1 Moyudan in academic year 2015/2016.This research belongs to educational research and development (R&D). The ten steps of R&D were modified based on Sukmadinata’s three main phases (2010:184), namely: (1) Exploration phase, which was conducted to describe the quality of the existing test administration administered to the first grade students of SMK Muhammadiyah 1 Moyudan and reveal the need of constructing alternative test for the first grade students of SMK Muhammadiyah 1 Moyudan, (2) Development phase, where the prototype model was constructed and evaluated, (3) Field Testing phase, in which the try out was administered. Data analysis was descriptive qualitative. Classroom observation, interview, and document analysis were used as the instruments of data collecting.The alternative test through QuizEgg was designed based on students’ needs. The use of QuizEgg as a test maker was very effective to design a test for students. The result of the developed alternative test administered to the students clearly indicated that the students were enthusiastic and motivated to do the test. Besides, it fulfilled the students’ needs and changed the way they did the test. In addition, the students’ achievement also improved, then, it could be seen by their mean score.